Monograph of Nylanderia (Hymenoptera: Formicidae) of the World, Part I: Nylanderia in the Afrotropics - Lapolla, John S.; Hawkes, Peter G.; Fisher, Brian L. (Zootaxa, 2011)
The taxonomy of the Afrotropical Nylanderia fauna is revised for the first time. Fourteen native species are revealed, of which eight are described as new: N. boltoni LaPolla and Fisher, N. brevisetula LaPolla and Fisher, N. impolita LaPolla and Fisher, N. luteafra LaPolla and Fisher, N. scintilla LaPolla and Fisher, N. silvula LaPolla and Fisher, N. umbella LaPolla and Fisher, and N. usambarica LaPolla, Hawkes and Fisher. Two species, N. jaegerskioeldi and N. natalensis, have workers that are indistinguishable from each other, and males are the only reliable way to separate these two species. Three non-native Nylanderia species are thought to have been introduced to Africa: N. bourbonica, N. vaga, and N. vividula. An identification key to the worker caste is provided.